Pengelolaan Dana Desa Sebagai Implikasi Berlakunya Undang – Undang Nomor 6 Tahun 2014 Tentang Desa “Di Desa Batursari, Kecamatan Mranggen, Kabupaten Demak” - Churrotul Ainiyyah; Kushandajani .; Puji Astuti (Journal of Politic and Government Studies, 2017)
ABSTRACTThe birth of the Village Act, namely Law number 6 of 2014 bring changes in the financialmanagement of the village, because the existence of Law of the village each get an extra sourceof income i.e. the village Fund (DD) estimated to be Rp 1.4 billion per year. The Batursarivillage is one of the recipients of the funding of the village as well as a recipient of funds (DD)the highest village in the Regency of Demak. With the income of the village with the sum high,certainly should be managed properly. If financial management of the village are not managedproperly, it will bring up a variety of issues.This research uses qualitative research methods with types of descriptive researchtechniques and data collection through interviews and documentation. The technique ofdetermination of informants in this study using a Purposive Sampling. As for thesubject/informants in this study is the head of the village, the village Secretary, Treasurer of thevillage, and BPD (Chairman) of the village of Batursari.The research indicates that the planning stages in the management of the village Fundthere are decision-making through deliberations undertaken the present hamlets to villages andinvolves elements of society. At this stage of implementation, the village Fund used properly aswell as the existence of the report and accountability for the use of the funds. At the stage ofmonitoring already exercised by the parties – the authorities do so. As for the implications of theexistence of the Village Laws against village fund management i.e. faster satisfy all the needsand wishes of the community, reporting APBDes using an application, its strategic role inescorting the BPD uses of the village Fund. However, the management of the Fund at the villageBatursari village can not be said to be fully transparent and accountable, yet the existence ofincome and expenditure details shapping Fund as well as the realization of the use of funds ofthe village on the information boards that are in the Hall of the village, the village so theGovernment must immediately pinned the financial details on the village Board the villageinformation so that the public is aware of and can supervise the use of the money.Keywords: Laws of the village, the Fund village, financial management